Industrial and Technological Applications of Transport in Porous Materials - Delgado, J.M.P.Q (Advanced Structured Materials, 2013)
The purpose of this book, Industrial and Technological Applications of Transport in Porous Materials, is to provide a collection of recent contributions in the field of heat and mass transfer in porous media and their industrial and technological applications. The main benefit of the book is that it discusses some of the most important topics related to transport phenomenon in engineering and their future applications. It includes a set of new technological applications in the field of heat and mass transfer phenomena in a porous medium domain, such as, drying technology, filtration, infrared thermography, energy, recycling, etc. At the same time, these topics will be going to the encounter of a variety of scientific and engineering disciplines, such as chemical, civil, agricultural, mechanical engineering, etc. The book is divided in several chapters that intend to be a resume of the current state of knowledge for benefit of professional colleagues.